Ria Ricis and New Platform of Islamic Popular Culture - Akmaliah, Wahyudi (DINIKA : Academic Journal of Islamic Studies, 2019)
Not only change the landscape of popular culture, but the presence of social media also reshapes the structure and the agency. Nowadays, social media can turn ordinary people to celebrities. Using Instagram and YouTube, Ria Ricis has become a piety celebrity who shows her Islamic identity through Islamic performance by wearing the veil in a casual way and earns money from her uploaded videos in social media. Based on a case study of this figure, this paper raises questions related to Islamic popular culture in Indonesia: How does Indonesian define their public sphere currently amid the growth of social media usage? How does Indonesian Muslim respond to social media as a part of digital technology amidst Islamization in the post of an authoritarian regime? What is the possibility of tension for that young Indonesian Muslim as micro-celebrity while facing the three factors related, Islamic identities, enjoyment, and economic benefits? This paper argues that the new media platform has not only affected Indonesian Muslimsâ€™ lifestyles, but also the way in which they negotiate Islamic values, secular life, and economic interest.Â Keywords: Ria Ricis, Social Media, Islamic Popular Culture, and Digital Economy